Patient Perspectives Regarding Allogeneic Bone Marrow Transplantation in Myelofibrosis - Palmer, Jeanne (Biol Blood Marrow Transplant, 2018)
Hematopoietic stem cell transplantation (HCT) is a curative treatment for patients with myelofibrosis (MF); however, many HCT-eligible patients decline this potentially life-saving procedure. The reasons behind this decision are not clear. We sought to survey patients with MF to understand their perspective on HCT. A 63-question survey was posted on myeloproliferative neoplasm patient advocacy websites. A total of 129 patients with MF responded to the survey. Among these patients, 49 (41%) were referred for HCT, and 41(32%) attended the transplantation consult. Of the patients who attended the transplantation consult, 24 (59%) did not plan on going on to HCT, and 16 (41%) intended to proceed with HCT. Reasons for the decision to not undergo transplantation included the desire to not be ill, desire to not spend time in the hospital, and concerns about overall quality of life. Specifically, concerns related to financial impact and the risk of graft-versus-host disease (GVHD) were expressed. Patients who decided to proceed with HCT felt that this would extend their survival and allow them to be around family for longer. This is the first survey to investigate patient perceptions regarding HCT for MF. Less than one-half of the patients were referred for HCT, and of those, less than one-half planned on proceeding with the transplantation, suggesting that many patients do not receive this life-saving procedure. Further exploration of the basis of patients’ reluctance to proceed with HCT is warranted.